The influence of flood pulses on the reproductive strategy of two species of passalid beetle in the fluvial archipelago of Anavilhanas, Amazon, Brazil - Mouzinho, José R.C.; Fonseca, Claudio Ruy Vasconcelos da; Barbosa, Márcio Luís Leitão (Journal of Natural History, 2010)
In environments subject to seasonal flood pulses, the level of the water influences the reproductive behaviour of the species Passalus abortivus and Passalus punctiger, which are beetles belonging to the family Passalidae. These species were studied in the fluvial archipelago of Anavilhanas, Negro River, State of Amazonas, Brazil, which floods annually for a period of six months. The results of this study show a negative and highly significant correlation between the level of the water and the presence of immature beetles. Our findings also indicate that both species show reproductive behaviour termed univoltine, which seems to be an adaptation to the limits imposed by the environmental conditions. En ambientes expuestos a pulsos de inundación estacional el nivel del agua actúa sobre el comportamiento reproductivo de las especies Passalus abortivus y Passalus punctiger, Coleópteros de la familia Passalidae. Estas especies fueron estudiadas en el Archipiélago fluvial Anavilhanas, Rio Negro, Estado de Amazonas, Brasil, el cual permanece anualmente inundado por un periodo de seis meses. Se encontró una correlación negativa y altamente significativa entre las variables nivel de agua y presencia de inmaduros. Nuestros resultados también indican que ambas especies muestran un comportamiento reproductivo denominado univoltino, que parece ser una adaptación a los límites impuestos por las condiciones ambientales. © 2010 Taylor & Francis.
Keywords: Archipelago; Beetle; Environmental Conditions; Flood Frequency; Fluvial Landform; Reproductive Strategy; Amazonas; Anavilhanas Archipelago; Brasil; Rio Negro [south America]; Coleoptera; Passalidae